RETOO: translating relational to object-oriented database conceptual schema - Soon, Lay Ki; Ibrahim, Hamidah; Mamat, Ali (Universiti Utara Malaysia, 2006)
The existence of multiple, heterogeneous and autonomous databases within an organization means the globally important information exists in separate local database management systems (DBMSs), thus making the existing data inaccessible to remote users. One solution is to integrate these databases in order to form a single cohesive definition of a multidatabase. Most of the integration is done by translating one database conceptual schema into another. In this paper, we will discuss a set of translation rules proposed to translate relational database conceptual schema into object-oriented database conceptual schema. A prototype called RElational-To-Object-Oriented (RETOO) has been developed based on our translation rules.